2005
DOI: 10.1002/app.21504
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and functionally superior starch–polyester nanocomposites from reactive extrusion

Abstract: Biodegradable starch-polyester polymer composites are useful in many applications ranging from numerous packaging end-uses to tissue engineering. However the amount of starch that can form composites with polyesters without significant property deterioration is typically less than 25% because of thermodynamic immiscibility between the two polymers. We have developed a reactive extrusion process in which high amounts of starch (approx. 40 wt%) can be blended with a biodegradable polyester (polycaprolactone, PCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 27 publications
2
41
0
2
Order By: Relevance
“…[19][20][21] Neutral polysaccharides, such as starch derived from corn, wheat, rice or potato, and cellulose and its derivatives, are the main biopolymers employed in the development of green nanocomposites. [23][24][25][32][33][34] These materials generally incorporate natural or synthetic clay minerals as inorganic nanofillers as well as organically modified clay minerals, giving intercalation or exfoliation compounds. Montmorillonite and cloisite are the usual silicates used in these studies, acting as nanocharges that can produce a reinforcing effect in the biopolymer matrix, thereby resulting in improved mechanical properties.…”
Section: Green Bionanocompositesmentioning
confidence: 99%
“…[19][20][21] Neutral polysaccharides, such as starch derived from corn, wheat, rice or potato, and cellulose and its derivatives, are the main biopolymers employed in the development of green nanocomposites. [23][24][25][32][33][34] These materials generally incorporate natural or synthetic clay minerals as inorganic nanofillers as well as organically modified clay minerals, giving intercalation or exfoliation compounds. Montmorillonite and cloisite are the usual silicates used in these studies, acting as nanocharges that can produce a reinforcing effect in the biopolymer matrix, thereby resulting in improved mechanical properties.…”
Section: Green Bionanocompositesmentioning
confidence: 99%
“…Organoclays show a better affinity towards non-polar species, which in this way may be assembled to the internal and the external surfaces of the modified clay mineral. Various authors have reported the preparation of bio-nanohybrid materials based on organoclays [137][138][139][140][141][142][143][144]. As this topic is specifically treated in Chapter 8, we will refer to it briefly here with some examples.…”
Section: Clay Minerals and Organoclay Bio-nanocompositesmentioning
confidence: 99%
“…[1][2][3] Thermoplastic starch has been produced using conventional thermal extrusion methods at suitable temperatures using added plasticizers (usually water and glycerol), and, in many cases, other polymer additives to modify the properties of starch-based materials. [4][5][6][7][8][9][10][11][12][13] Polymer-clay nanocomposites have attracted a great deal of interest by researchers in academia and industry, because significant improvements in many aspects of material performance can be obtained when using a very low dosing amount of such layered nanoparticles. [14][15][16][17][18][19] The property improvements of these doped materials compared with pure polymers or conventional micro-or macrocomposites are due to the significantly strengthened interfacial interactions between polymer chains and nanoparticles (layer thickness of the order of 1 nm, diameter of 30-1000 nm) when these particles are well dispersed in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%